Influence of Brand Ambassador and Brand Image on Shopee Purchases with Brand Trust Mediation - Firdaus Firdaus; Wa Ode Sitti Nurrahmah; M. Roby Jatmiko; Kukuh Mulyanto; Asepta Hendriyanto (Universitas Muhammadiyah Semarang, 2025)
This study aims to examine the influence of brand ambassadors and brand image on purchase decisions in the Shopee application, with brand trust as an intervening variable. A quantitative approach was used, involving 100 respondents selected through purposive sampling. Data were collected via an online questionnaire using a Likert scale of 1-5 and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that brand ambassadors have a significant positive effect on brand trust but do not significantly influence purchase decisions. Meanwhile, brand image has a significant positive effect on both brand trust and purchase decisions. However, brand trust does not significantly influence purchase decisions. Additionally, brand trust does not significantly mediate the relationship between brand ambassadors and purchase decisions, nor between brand image and purchase decisions. These findings highlight the importance of brand image in driving consumer trust and purchase behavior, while the role of brand ambassadors appears to be more indirect. This research provides valuable insights for e-commerce platforms and businesses in optimizing their marketing strategies by focusing on brand image development and strategic brand ambassador selection.